2008
DOI: 10.3329/bjp.v4i1.1211
|View full text |Cite
|
Sign up to set email alerts
|

In vitro glucose uptake by isolated rat hemi-diaphragm study of Aegle marmelos Correa root

Abstract: The methanol extract of the root of Aegle marmelos, a medicinal plant, was fractionated into eight fractions using column chromatography. The antidiabetic activity of all the fractions was studied using the glucose uptake by isolated rat hemi-diaphragm in vitro model. Using the bioassay-guided fractionation, two compounds 1 and 2 were isolated by column chromatography and identified as 6-methyl-4-chromanone and skimmianine respectively by NMR and mass spectral methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…The possible reason for the observed attenuation of glucose uptake (transport) promoting activity of the alcoholic extracts compared to insulin could be the presence of other interfering substances in the crude extracts that reduce the potential of the promoting molecules. Presence of phytochemicals in alcoholic extracts of other plants, which promote glucose uptake in muscle and adipose cell lines [ 21 - 23 ], substantiate our observed effect.…”
Section: Discussionsupporting
confidence: 82%
“…The possible reason for the observed attenuation of glucose uptake (transport) promoting activity of the alcoholic extracts compared to insulin could be the presence of other interfering substances in the crude extracts that reduce the potential of the promoting molecules. Presence of phytochemicals in alcoholic extracts of other plants, which promote glucose uptake in muscle and adipose cell lines [ 21 - 23 ], substantiate our observed effect.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Panda and Kar () reported that scopoletin has potent antioxidative activities and it is able to regulate hyperglycemia and diabetic complications in rats. Both skimmianine and melicarpinone are quinolone alkaloids that have anti‐inflammatory activity and maybe responsible for the in vitro antidiabetic effects (Ravi and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Ethnopharmacological and ethno botanical surveys indicate that more than 1200 plants are used worldwide in herbal medicine to treat diabetes (Ziyyat et al, 1997;El-Hilaly et al, 2003;Tahraoui et al, 2007 (Prajapati et al, 2008;Ravi et al, 2009;Pattanayak et al, 2009;Tatiya et al, 2013;Bandara et al, 2009;Saha et al, 2009;Bhowmik et al, 2009;Sen et al, 2013;Khanam et al, 2009;Alamgeer et al, 2013;Bhavsar and Talele, 2013;Kulandaivel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%